Phenotype characterization of embryoid body structures generated by a crystal comet effect tail in an intercellular cancer collision scenario (2012)
Cancer is, by definition, the uncontrolled growth of autonomous cells that eventually destroy adjacent tissues and generate architectural disorder. However, this concept cannot be totally true. In three well documented studies, we have demonstrated that cancer tissues produce order zones that evolve over time and generate embryoid body structures in a space-time interval. The authors decided to revise the macroscopic and microscopic material in well-developed malignant tumors in which embryoid bodies were identified to determine the phenotype characterization that serves as a guideline for easy recognition. The factors responsible for this morphogenesis are physical, bioelectric, and magnetic susceptibilities produced by crystals that act as molecular designers for the topographic gradients that guide the surrounding silhouette and establish tissue head-tail positional identities. The structures are located in amniotic-like cavities and show characteristic somite-like embryologic segmentation. Immunophenotypic study has demonstrated exclusion factor positional identity in relation to enolase-immunopositive expression of embryoid body and human chorionic gonadotropin immunopositivity exclusion factor expression in the surrounding tissues. The significance of these observations is that they can also be predicted by experimental image data collected by the Large Hadron Collider (LHC) accelerator at the European Organization for Nuclear Research, in which two-beam subatomic collision particles in the resulting debris show hyperorder domains similar to those identified by us in intercellular cancer collisions. Our findings suggest that we are dealing with true reverse biologic system information in an activated collective cancer stem cell memory, in which physics participates in the elaboration of geometric complexes and chiral biomolecules that serve to build bodies with embryoid print as it develops during gestation. Reversal mechanisms in biology are intimately linked with DNA repair. Further genotype studies must be carried out to determine whether the subproducts of these structures can be used in novel strategies to treat cancer. © 2012 Diaz and Murillo, publisher and licensee Dove Medical Press Ltd.